Neuronal intranuclear inclusion disease with subtle imaging findings: a case report and literature review - Tian Zhang; Xiaoying Zhang; Jiehua Ma; Ziyang Huang; Yuwen Wang; Meiduo Gesang; Chenling Hu (BMJ Neurology Open)
Introduction Neuronal intranuclear inclusion disease (NIID) is a rare neurodegenerative disorder. Hyperintense signals on diffusion-weighted imaging (DWI) at the corticomedullary junction are key diagnostic features. Early manifestations are often overlooked, leading to misdiagnoses. Here, we report a case of adult-onset NIID with DWI hyperintensities at the corticomedullary junction.Case presentation A 72-year-old woman presented with progressive memory deterioration starting 9 years ago. In the third year, MRI showed extensive white matter lesions and brain atrophy, with focal high signal intensity in the corticomedullary junction of the frontal lobe; however, this was overlooked. The patient was clinically diagnosed with Alzheimer’s disease. In the seventh year, the patient gradually developed emotional instability, bradykinesia and urinary incontinence. In the eighth year, MRI revealed a remarkable curvilinear DWI hyperintense signal at the corticomedullary junction. Further genetic testing identified 105 GGC repeats in the NOTCH2NLC gene. Skin biopsy revealed intranuclear inclusions in P62 and ubiquitin-positive fibroblasts, confirming the NIID diagnosis.Conclusions Patients with NIID show characteristic DWI hyperintensity at the corticomedullary junction during symptoms. This early imaging finding is subtle and often overlooked. For patients with dementia and episodic encephalopathy, observing radiological changes, along with genetic and skin biopsies, is indispensable.